2021
DOI: 10.3390/biology10040306
|View full text |Cite
|
Sign up to set email alerts
|

3D Imaging and Quantitative Characterization of Mouse Capillary Coronary Network Architecture

Abstract: Characterization of the cardiac capillary network structure is of critical importance to understand the normal coronary functional properties and coronary microvascular diseases. The aim of our study was to establish an accessible methodology for 3D imaging and 3D processing to quantitatively characterize the capillary coronary network architecture in mice. Experiments were done on C57BL/6J mice. 3D imaging was performed by light sheet microscopy and confocal microscopy on iDISCO+ optical cleared hearts after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…According to a previous study on heart, we established that, as in the brain, the volume shrinkage was minor, around 19%, without deformation [17]. Our results showed an estimated kidney volume shrinkage around 30%, without significant difference in each dimension, suggesting that, compared to the brain and heart, the iDISCO+ method induced a higher shrinkage, though isotropic, in kidneys.…”
Section: D Imagingsupporting
confidence: 61%
“…According to a previous study on heart, we established that, as in the brain, the volume shrinkage was minor, around 19%, without deformation [17]. Our results showed an estimated kidney volume shrinkage around 30%, without significant difference in each dimension, suggesting that, compared to the brain and heart, the iDISCO+ method induced a higher shrinkage, though isotropic, in kidneys.…”
Section: D Imagingsupporting
confidence: 61%
“…The fluorescently labeled vasculature can be visualized by confocal microscopy throughout the entire heart after tissue clearing (Kolesov a et al, 2021). Recently faster and high-quality 3D imaging of coronary vasculature is possible using light sheet microscopy (Nicolas & Roux, 2021).…”
Section: Methods For Visualizing Coronary Microvasculature During Emb...mentioning
confidence: 99%
“…Coronary microvasculature can be also visualized by plasma membrane staining using lectin WGA that binds to glycoproteins on the cell surface (Figure 1c,d). Recently, the protocol for quantifying the coronary capillary three‐dimension (3D) architecture has been established by using a combination of light sheet with labeling of the capillary endothelium by lectin injection into vessels (Nicolas & Roux, 2021).…”
Section: Methods For Visualizing Coronary Microvasculature During Emb...mentioning
confidence: 99%
“…Few 3D algorithms have been proposed in the literature as applied to in vivo images. [23][24][25] They are based on similar steps, segmentation, and skeletonization, leveraging distance mapping to compute different network features. Furthermore, they take advantage of the third dimension considering a volumetric vascular density.…”
mentioning
confidence: 99%
“…In addition, the method can provide the fractal dimension, the number of segments, vessel length, diameter, and tortuosity. 23 These methods have shown that the third dimension can add important information to the analysis, more properly evaluating the 3D system. The circularity of the vessel cross-section represents a clear example of how the 3D information might be used to enhance the characterization of the model.…”
mentioning
confidence: 99%